Campur Kode dalam Video Dakwah Ustaz Hanan Attaki dan Ustaz Felix Siauw di Youtube: Kajian Sosiolinguistik - Tetri Alia Nova; Yetty Morelent; Syofiani Syofiani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study analyzes the sociolinguistic phenomenon of mixed language use in digital preaching. The study focuses on the communication styles of two well-known preachers, Ustaz Hanan Attaki (UHA) and Ustaz Felix Siauw (UFS), on YouTube. The aim of this study is to describe the types, reasons, functions, and comparisons of mixed language use by these two figures. The approach used was descriptive qualitative, with data analysis methods consisting of speech in video lectures on their official channels. The research findings identified 72 data points related to mixed language, consisting of five types: word insertion, phrase insertion, clause insertion, word repetition, and bastering. The most common types were word insertion and clause insertion. Reasons for code-mixing include the use of more easily understood popular terms, the connection of themes to references from the Quran and Hadith, the speakers' backgrounds, and efforts to adapt to audiences from millennials and Gen Z. Functionally, code-mixing is used to facilitate communication, create a more relaxed atmosphere, and explain Islamic concepts that are difficult to find equivalents in Indonesian. Comparatively, UHA tends to use Arabic code-mixing more often for spiritual matters, while UFS uses English more for aspects of logic and modern lifestyle. The research concludes that code-mixing is a flexible sociolinguistic strategy for connecting sacred religious messages with the current social dynamics of audiences.